2024
DOI: 10.1186/s40644-024-00659-x
|View full text |Cite
|
Sign up to set email alerts
|

MR radiomics predicts pathological complete response of esophageal squamous cell carcinoma after neoadjuvant chemoradiotherapy: a multicenter study

Yunsong Liu,
Yi Wang,
Xin Wang
et al.

Abstract: Background More than 40% of patients with resectable esophageal squamous cell cancer (ESCC) achieve pathological complete response (pCR) after neoadjuvant chemoradiotherapy (nCRT), who have favorable prognosis and may benefit from an organ-preservation strategy. Our study aims to develop and validate a machine learning model based on MR radiomics to accurately predict the pCR of ESCC patients after nCRT. Methods In this retrospective multicenter st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Prior studies revealed that PORT could enhance OS in carefully selected patients; however, these studies were based solely on clinical features and lacked external validation [ 13 , 14 ]. Radiomics, which use quantitative imaging characteristics, has emerged as a promising tool for disease diagnosis and prognosis [ 22 ]. Our study showed that the RPI was a promising marker, and LRPI could identify patients who would benefit from PORT.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies revealed that PORT could enhance OS in carefully selected patients; however, these studies were based solely on clinical features and lacked external validation [ 13 , 14 ]. Radiomics, which use quantitative imaging characteristics, has emerged as a promising tool for disease diagnosis and prognosis [ 22 ]. Our study showed that the RPI was a promising marker, and LRPI could identify patients who would benefit from PORT.…”
Section: Discussionmentioning
confidence: 99%